Experimental Evaluation of Estimating Living-Body Direction Using Array Antenna for Multipath Environment - Konno, Keita; Nango, Masaki; Honma, Naoki; Nishimori, Kentaro; Takemura, Nobuyasu; Mitsui, Tsutomu (IEEE antennas and wireless propagation letters, 2014)
In this letter, we introduce a method that uses the radar system to observe the waves reflected from the target with the single-input-multiple-output (SIMO) array configuration to estimate living-body directions in a multipath environment for applications such as elderly monitoring. Directions of living body are estimated by the MUltiple SIgnal Classification (MUSIC) method, where the Fourier transformed channel matrix is used. Our use of the 2.4-GHz band allows greater miniaturization of the antenna than is possible with the low-frequency band used by conventional systems. Also, this method can be used in multipath-rich environments such as indoors. The experiments are carried out in a specific indoor environment as a demonstration, and the SIMO channel is measured with various subject numbers and positions. The results indicate that the proposed method can estimate living-body directions with high accuracy even in multipath environments.